Advancing Social Justice Work at the Intersections of Multiple Privileged Identities. Issue 157 (March 2017) - Kendall, Frances E.; Wijeyesinghe, Charmaine L.
Abstract : The authors discuss how the concept of social location and tenets of intersectionality inform the understanding of power and privilege, our work with people with multiple privileged identities, and the preparation of social justice educators.